A steam-based pedagogical model for developing technical thinking in primary school students - Yessaliyev, Aidarbek A.; Totikova, Guldana A.; Medetbekova, Nurgul N.; Zhiyasheva, Zhanar Sh. (International Journal of Innovative Research and Scientific Studies, 2025)
In the context of global technological transformation and the implementation of technological modernization strategies in Kazakhstan, the development of design and technical thinking (DTT) in primary school students becomes a critically important task. The aim of this study was to develop and test a pedagogical model based on an interdisciplinary STEAM approach (science, technology, engineering, arts, mathematics) and adapted to the specifics of the Kazakhstani education system. The model was developed through a theoretical synthesis of current research in STEAM education and psychological–pedagogical theories and comprises four interrelated stages: Motivational–Orientation, Project–Research, Experimentation–Analysis, and Reflective–Presentation. A school-based approbation in Shymkent (172 learners in Grades 1–4; 4 teachers) employed classroom observation, class-embedded diagnostic tasks, and brief self-reports to monitor feasibility and acceptability. Aggregated monitoring indicated 20–30% gains on indicators of independent problem formulation and stepwise solution planning; the share of learners at the “high” level rose from 26% to 43% for algorithmic (procedural) thinking and from 18% to 36% for divergent thinking. These findings are feasibility signals rather than causal estimates, suggesting practical implementability under routine conditions and motivating a subsequent controlled evaluation and scaling across diverse educational contexts in Kazakhstan.